Disrupted establishment of anaerobe and facultative anaerobe balance in preterm infants with extrauterine growth restriction - Huang, Yi-E; Shen, Xintian; Yin, Dingding; Lan, Shanwei; Lu, Yongxue; Zhou, Ping; Ma, Liya; Zhang, Yinlan; Sheng, Yuhui; Zhang, Youjun; Li, Mengna; Hu, Fei; et al. (Frontiers in Pediatrics, 2022)
Background Extrauterine growth restriction (EUGR) in preterm birth infants could have long-term adverse impacts on health. Less is known about the gut microbiota regarding its establishment in early life and its role in long-term growth in preterm birth infants. Methods A prospective, longitudinal observational study was conducted with 67 preterm infants in a level III neonatal intensive care unit. Clinical information was obtained from medical records, and fecal samples were collected weekly during hospitalization and processed for 16S rRNA gene sequencing. Results The bacterial profiles from the weekly sampling of preterm infants demonstrated that the early-life gut microbiota was clustered into the following four stages in chronological order: stage 1: 0–4 days, stage 2: 1–2 weeks, stage 3: 3–7 weeks, and stage 4: 8–10 weeks. The development of gut microbiota showed latency at stage 4 in EUGR infants compared with that in non-EUGR infants, which resulted from their consistently high level of facultative anaerobes, including Enterobacteriaceae and Staphylococcus, and lack of obligate anaerobes, including Clostridium and Veillonella. In the 2-year follow-up, infants with a high level of obligate anaerobes-to-facultative anaerobes ratio at stage 4 had a lower risk of long-term growth restriction at the margin of statistical significance. Conclusion The results of this study indicate that the development of gut microbiota in the early life of EUGR infants is delayed compared with that of non-EUGR infants. The obligate-to-facultative anaerobes ratio could be an indicator of the maturity of gut microbiota development and associated with the risk of long-term growth restriction in preterm infants.